Abnormal gene expression leads to poor prognosis in breast cancer patients in Bihar. (July 2016) - Anshu, Aseem; Nath, Akhileshwari; Prinyanka,; Sinha, Neha; Sinha, Priyanka; Sinha, Shreya; Singh, J.
Abstract With its highest mortality rate, the breast cancer outruns other gynecological cancers. For a long time, the breast cancer was associated with poor prognosis. But with the advent of analysis of expression level of different protein receptors (ER/PR and Her-2/neu) with the help of immunohistochemistry (IHC) has ushered us to a new era of treatment of cancer called immunotherapy. Tissues sampled from 167 breast cancer patients at pathology labs of Mahavir Cancer Institute & Research Center, S S Hospital and Research Institute and NMCH, Patna, Bihar, India, were processed by a routine protocol. Highest percentage of patients showed ER+ /PR+ and least percentage of patients were characterized by ER+/PR− (p value <0.0001, hazard ratio, 95 % CI 2.537–21.603). A large number of patients (52.09 %) were classified under luminal C. Interestingly, 25.74 and 44.31 % of total patients aged within 30–50 tend to show ER− /PR− and Her-2/neu withp value <0.0081 (hazard ratio, 95 % CI 1.674–6.833) and 0.0313 (hazard ratio, 95 % CI 0.263–1.623), respectively. The present endeavor was to classify the patients for their prognosis on the basis of hormonal and C-erb B2. The failure of the drug in ER−/PR− patients like tamoxifen is not a good sign to the oncologists. Herceptin on the other hand can play a good role in the treatment of greater percentage of patients showing Her-2/neu+. However, implementation of either new prognostic marker or more effective immunotherapy or both are warranted for effective treatment of breast cancer patients.